2009
DOI: 10.1111/j.1743-6109.2009.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual, Marital, and Social Impact of a Man’s Perceived Infertility Diagnosis

Abstract: Introduction Male factor infertility is a relatively common problem. This diagnosis may increase sexual, marital, and relationship strain in male partners of infertile couples. Aim To measure the personal, social, sexual, and marital impacts of a male factor infertility diagnosis among men in couples evaluated for infertility. Methods Cross-sectional analysis of 357 men in infertile couples from eight academic and community-based fertility clinics. Participants completed written surveys and face-to-face an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 42 publications
3
107
2
5
Order By: Relevance
“…Neither age nor cause of infertility was related to sexual satisfaction, but it was negatively related (P,0.01) to duration of time since diagnosis. In a study by Smith et al 42 for men with male factor infertility or in couples with unexplained infertility, there were lower levels of sexual quality of life, assessed by enjoyment, sense of attractiveness to the intimate partner and intrusiveness of thoughts about fertility problems and wanting a child during intercourse. In the study by Tüzer et al 46 in Turkey, fewer men (20%) than women (44%) reported that sexual interest had decreased since infertility diagnoses.…”
Section: Consequences Of Infertility For Intimate Partner Relationshimentioning
confidence: 99%
“…Neither age nor cause of infertility was related to sexual satisfaction, but it was negatively related (P,0.01) to duration of time since diagnosis. In a study by Smith et al 42 for men with male factor infertility or in couples with unexplained infertility, there were lower levels of sexual quality of life, assessed by enjoyment, sense of attractiveness to the intimate partner and intrusiveness of thoughts about fertility problems and wanting a child during intercourse. In the study by Tüzer et al 46 in Turkey, fewer men (20%) than women (44%) reported that sexual interest had decreased since infertility diagnoses.…”
Section: Consequences Of Infertility For Intimate Partner Relationshimentioning
confidence: 99%
“…Other authors suggested that infertility may be stressful but can provide common grounds for closer mutual support to thoughts and feelings of couples and, therefore, has a positive effect on couples' relationship and sexual behaviors [27,43]. A lack of effect of male infertility on marital relationships has been suggested in other studies [23].…”
Section: Discussionmentioning
confidence: 92%
“…Studies have also showed that sexual assertiveness and self-esteem are two important factors that can affect sexual satisfaction levels [22]. Murphy found that low self-esteem and overall low sexual assertiveness are the personality traits of women who have experienced sexual coercion in their marital relationships [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported a dramatic decrease in couples' conjugal quality of life and relationships. These impairments, similar to other psychosocial complications of infertility, may vary according to the economic, occupational, educational, social, and religious characteristics of couples (11,12). Benazon et al (13) reported a lower prevalence of marital adjustment disorders among infertile couples who were successfully treated by assisted reproductive technologies (ART) than infertile couples without ART in the first year of infertility.…”
Section: Introductionmentioning
confidence: 99%